The Use of Zoom Application As Teaching Media To Improve Students’ Speaking Skill - Dharmawati Dharmawati (Institut Agama Islam Negeri Palopo, 2022)
This study seeks to investigate the use of zoom application as teaching media to improve students’ speaking skill. Zoom application becomes the most popular tool in teaching learning process for pandemic era, especially in teaching speaking The main purpose of this study how to improve students’ speaking skill in English by using zoom application. It allows students and lecturer to make calls, send messages and do video conferencing online. This study was action research by combining quantitave and qualitative. The subject of this study was 25 second semester students of informatics department at Universitas Harapan Medan in the academic year of 2020/2021. The data were in the forms of qualitative and quantitative. The qualitative data were obtained by observing the teaching and learning process of speaking and interviewing and the quantitave data were acquired through pre-test and post-test. The result of the study showed the improvement the students’ score from 6.9 in pre-test to 13.29 in the post-test proved that teaching English using zoom application was able to improve their speaking skill. The procedure of improving speaking skill by using zoom application consists of preparation, presentation, practice, evaluation and expansion.